MODELING PROFITABILITY IN RICE FARMING UNDER PHILIPPINE RICE TARIFFICATION LAW: AN ECONOMETRIC APPROACH - Leomarich F. CASINILLO (Scientific Papers Series : Management, Economic Engineering in Agriculture and Rural Development)
This research study aimed to elucidate the significant predictors of profitability in rice farming under the implementation of the Rice Tariffication Law (RTL) in the Philippines. Data from 177 rice farmers in Hilongos, Leyte, Philippines were analyzed using descriptive analysis and econometric modeling. Results showed that the profitability of rice farmers is decreasing since the implementation of RTL in the country. This happens because of a large supply of rice (imported) in the country which resulted in a decrease in farmers' produce rice marketability price. Meanwhile, the agricultural inputs during RTL are also high. The econometric model has revealed that there are only a few significant predictors of profitability in rice farming during the implementation of RTL such as leisure time (p-value=0.076), perception of government (Scale of 1 to 10; p-value<0.001), and farm assets (p-value<0.001). Conclusively, farmers must reduce their allotted time for unnecessary leisure activities and engage more in productive farming activities to increase economic profit amid the promulgated RTL. The results suggested that government support and development program is needed for the poor farmers' sustainability especially in rural areas to continue during the implementation of RTL. The local government must take an initiative to form farmers' associations and cooperatives to provide for farmers' needs and can access credit for farm inputs. Furthermore, the government must provide training and seminars for farmers concerning RTL to become aware and knowledgeable about the pros and cons of the policy.